Archived data from Northern Circumpolar Soil Carbon Database - Bolin Centre for Climate Research (Stockholm University, 2018)
The Northern Circumpolar Soil Carbon Database (NCSCD) is a geospatial database created for the purpose of quantifying storage of organic carbon in soils of the northern circumpolar permafrost region.

The spatial base of the NCSCD is a polygon database describing soils in the northern circumpolar permafrost regions. The database was compiled by combining and homogenizing several regional/national soil maps. To calculate storage of soil organic carbon, these soil maps have been linked to field-data on soil organic carbon storage from a total of 1,647 sites from around the circumpolar permafrost region.

The NCSCD contains information on fractions of coverage of different soil types (following U.S. Soil Taxonomy nomenclature) as well as storage of soil organic carbon (kg/m2) between 0-30 cm and 0-100 cm depth. The NCSCD is available either as a polygon-based database (which is the original format) or converted to gridded data. Gridded data products are available in different spatial grid resolutions and in formats adapted for use in desktop GIS-applications and model applications.

Archived data from Northern Circumpolar Soil Carbon Database version 1, 2016-05-26. For later versions of data go to https://bolin.su.se/data/ncscd/.

Archived data from Northern Circumpolar Soil Carbon Database version 1, 2019-05-26.

The Northern Circumpolar Soil Carbon Database (NCSCD) är en geospatial databas som skapats för att kvantifiera lagring av organiskt kol i marken i den nordliga cirkumpolära permafrostregionen.

Arkiverad data för Northern Circumpolar Soil Carbon Database version 1, 2016-05-26. För senare versioner av data gå till https://bolin.su.se/data/ncscd/.

För mer utförlig beskrivning se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/ecds0148

Archived data from Northern Circumpolar Soil Carbon Database version 1, 2016-05-26.
Archived data from Northern Circumpolar Soil Carbon Database
Keywords: CARBON; PERMAFROST; SOIL CLASSIFICATION; PERMAFROST; CRYOSOLS; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Geoscientific Information; Geovetenskap